The technician. - MSU-Iligan Institute of Technology (Iligan City Mindanao State University, Iligan Institute of Technology)
Research on scientific, technological, ecological and social conditions, especially pertaining to the southern Philippines.
Official journal of the MSU-Iligan Institute of Technology, Dec. 1983-
Keywords: Science; Engineering; Social sciences; Humanities; Research -- Philippines